Unlocking Randuwana's Enchantment: Umsida's Transformative Role in Elevating Sapta Pesona in Enchanting Village Pools: Membuka Pesona Randuwana: Peran Transformatif Umsida dalam Mengangkat Sapta Pesona di Kolam Desa yang Mempesona - Laksono, Muhammad Agung; Sudarso, Satrio; Alfia, Nurfia; Rohma, Ainun Nur (International Consortium of Education and Culture Research Studies, 2023)
The aim of this service is to improve community empowerment, help local communities by providing education and training on village pool management, tourism management and promotion of local destinations. The service methods applied are training and workshops to provide local community training about managing village ponds, increasing tourism and environmental curiosity. The result of this service is that there is more local community participation in the management and promotion of the Village Pool, giving them a sense of ownership and responsibility for their tourist destination, which attracts more tourists. The implication of this service is that community economic empowerment in the tourism sector can increase local community income and have a positive economic impact. Highlight: Community Involvement: Enhanced local participation in managing and promoting the Village Pool empowers the community, fostering a sense of ownership and responsibility for their tourist destination. Economic Empowerment: Through tourism sector engagement, there's potential for increased local income, showcasing positive economic impacts on the community. Service Methodology: Training and workshops serve as effective tools for educating and empowering local communities in village pond management and tourism promotion, fostering environmental curiosity. Keyword: Sapta Pesona, Community empowerment, Tourism Village, Local Destinations